Microstructure and Perfusion Alterations of Globus Pallidus in Neonates with Hyperbilirubinemia - Zhang, Yi; Zhang, Juan; Chen, Yu-Chen; Zheng, Jin-Xia; Ding, Shaohua (Current Medical Imaging, 2024)
Background: Previous studies have indicated the abnormality of the globus pallidus in neonates with hyperbilirubinemia. Objective: This study aims to explore the microstructure and cerebral perfusion of globus pallidus in neonatal hyperbilirubinemia by using Diffusion Tensor Imaging (DTI) and Arterial Spin Labeling (ASL) approaches. Methods: Thirty-seven neonates were enrolled in this study, which were classified into Bilirubin-Induced Neurologic Dysfunction (BIND) group (hyperbilirubinemia with BIND, n=12), non-BIND group (hyperbilirubinemia without BIND, n=15), and healthy controls (HC) group (n=10). The quantitative values of globus pallidus were calculated from DTI, including the Apparent Diffusion Coefficient (ADC), the Fractional Anisotropy (FA), and Volume Ratio (VR) values. Additionally, the relative Cerebral Blood Flow (rCBF) values were obtained from ASL. Results: It was observed that the mean DTI signal of globus pallidus was significantly different among the three groups (p < 0.05). However, there were no significant differences in the rCBF of globus pallidus among the three groups (p > 0.05). A positive correlation was also observed between the fractional anisotropy (FA) value and serum bilirubin level (r = 0.561, p = 0.002), while the VR value showed a negative correlation with serum bilirubin level (r=-0.484, p=0.011). The area under the curve (AUC) of FA, VR, and FA and VR combined was 0.897, 0.858, and 0.933, respectively. Conclusion: The alterations of microstructure in globus pallidus, especially FA and VR value, may be valuable and sensitive at the early stage of hyperbilirubinemia encephalopathy, suggesting that early hyperbilirubinemia may lead to cytotoxic edema and decreased permeability of the cell membrane.
Keywords: Arterial spin labeling